2007
DOI: 10.1371/journal.pcbi.0030121
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Function in the “Two Dinucleotide Binding Domains” Flavoproteins

Abstract: Structural and biochemical constraints force some segments of proteins to evolve more slowly than others, often allowing identification of conserved structural or sequence motifs that can be associated with substrate binding properties, chemical mechanisms, and molecular functions. We have assessed the functional and structural constraints imposed by cofactors on the evolution of new functions in a superfamily of flavoproteins characterized by two-dinucleotide binding domains, the “two dinucleotide binding dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 54 publications
2
69
0
Order By: Relevance
“…This caution aside, the report opens up the long studied flavin-dependent thioredoxin reductase family for further exploration. These enzymes belong to a broader disulfide oxidoreductase family of flavoenzymes (lipoamide dehydrogenase, glutathione reductase, trypanothione reductase, mercuric reductase, and NADH peroxidase), which are known for the diversity of their substrates (46). However, the members that have been studied thus far are nicotinamidedependent, and the possibility that some of the uncharacterized members use other types of electron carriers has not been explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This caution aside, the report opens up the long studied flavin-dependent thioredoxin reductase family for further exploration. These enzymes belong to a broader disulfide oxidoreductase family of flavoenzymes (lipoamide dehydrogenase, glutathione reductase, trypanothione reductase, mercuric reductase, and NADH peroxidase), which are known for the diversity of their substrates (46). However, the members that have been studied thus far are nicotinamidedependent, and the possibility that some of the uncharacterized members use other types of electron carriers has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Because of high sequence similarities between flavin-containing thioredoxin reductases and other pyridine dinucleotide oxidoreductase family proteins (46), especially the alkyl hydroperoxide reductases, we employed a two-step method involving the following for the identification of DFTR homologs: identification of candidates via Psi-BLAST searches (47) using Mj-DFTR (locus number, MJ1536) as a query and with stringent parameters (low e-value, 1e Ϫ25 ; 10 iterations); phylogenetic analysis-based screening of the candidates. Such an analysis of the extracted methanogen proteins suggested that within this group the DFTR homologs were limited to the phylogenetically deeply rooted methanogens belonging to the class of Methanococci under the euryarchaeal phylum, and these organisms lacked NTR and ferredoxin-thioredoxin reductase (FTR) homologs ( Fig.…”
Section: Distribution and Phylogenetic Clades Of Dftr Homologsmentioning
confidence: 99%
“…FMOs, BVMOs, and NMOs are each distinguished by variations in primary structural motifs, substrate preferences, and catalytic mechanisms. FMOs are also notably similar to the Group A enzymes dihydrolipoamide dehydrogenase (DLD), glutathione reductase (GR), and low-molecular-weight thioredoxin reductase (TRXR) (2,4). These groups are distinguished from other flavin-dependent monooxygenases (Groups C-H) by their combined use of FAD and NAD(P)H. Any functional interplay between FMOs and Group A enzymes, perhaps as an NAD(P)H-thiol redox buffering system, is largely unexplored (5).…”
Section: Evolution and Classificationmentioning
confidence: 99%
“…Given the complexity of the relationship between sequence, structure and function divergence in proteins sensu lato, a sensible approach is to study these relationships in the limited context of individual families, superfamilies and structural folds (for several recent examples of such studies, see [19][20][21][22][23]). In fact, functional diversity within a given fold or superfamily can span a wide variety of different molecular activities and biological processes, and studies of large and diverse superfamilies are particularly relevant given the recent evidence that they are more likely to contain proteins with essential functions [24].…”
Section: How Does Function Evolve Within Superfamilies?mentioning
confidence: 99%
“…Divergence of function amongst homologues can result from several mechanisms such as substitutions in the active sites [27], changes in residues that determine the specificity of interactions (see [28;29] for recent methods that exploit this principle), or variation in environmental context such as the presence of other potential protein interaction partners [23]. However, one conclusion derived from the analysis of the data in the SFLD is that many functionally divergent enzyme superfamilies seem to conserve a common partial reaction or other chemical capability [26].…”
Section: How Does Function Evolve Within Superfamilies?mentioning
confidence: 99%